HIDEA syndrome: A new case report highlighting similarities with ROHHAD syndrome - Harvengt, J.; Lumaka, A.; Fasquelle, C.; Caberg, J. H.; Mastouri, M.; Janssen, A.; Palmeira, L.; Bours, V. (Frontiers in Genetics, 2023)
Context : ROHHAD syndrome present significant resemblance to HIDEA syndrome. This last entity is caused by bi-allelic loss of function variants in P4HTM gene and encompasses Hypotonia, Intellectual Disabilities and Eye Abnormalities, Hypoventilation and Dysautonomia. We report the first HIDEA syndrome patient identified from our ROHHAD cohort. Clinical Case : This 21-month-old girl had a history of severe respiratory infections requiring intensive care, hypotonia, abnormal eye movements and rapid weight gain. A polysomnography identified a severe central hypoventilation. During her follow-up, a significant psychomotor delay and absence of language were gradually observed. Prolactin levels were initially increased. Hypothermia was reported at 4 years. Exome sequencing identified a new homozygous truncating P4HTM variant. Discussion : Our patient encountered diagnosis criteria for ROHHAD including a rapid weight gain, central hypoventilation appearing after 1.5 years of age, hyperprolactinemia suggesting a hypothalamic dysfunction and an autonomic dysfunction manifesting as strabismus and hypothermia. However, she also presented with a severe neurodevelopmental delay, which is not a classic feature of ROHHAD syndrome. HIDEA Syndrome presents similarities with ROHHAD including Hypoventilation, Obesity, and Dysautonomia. Until now, only 14% of endocrinological disturbances have been reported for HIDEA patients. Better delineation of both syndromes is needed to investigate eventual involvement of P4HTM, a regulator of calcium dynamics and gliotransmission, in ROHHAD patients. Conclusions : In case of clinical evidence of ROHHAD in a child with abnormal neurological development or eye abnormalities, we suggest that the P4HTM gene should be systematically interrogated in addition to the PHOX2B analysis. A better delineation of the natural history of HIDEA is required to allow further comparison between HIDEA and ROHHAD features. The clinical similarities could potentially orient some molecular hypotheses in the field of ROHHAD research.